Preparation method of three-layer co-extrusion film for soft cigarette box packaging
Through the preparation method of the three-layer coextruded film, the formulation and process of the inner layer, core layer and outer layer are adjusted, and the challenges of cigarette soft box packaging film in sealing performance, flexibility and optical performance are solved, achieving efficient packaging effect and degradable performance.
Patent Information
- Application Number
- CN202411904406.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing cigarette packaging films are difficult to balance good sealing performance, flexibility and optical properties in the domestic market, especially in the packaging of cigarette soft box.
The preparation method of three-layer co-extruded film is adopted. By adjusting the formulation and process of the inner layer, core layer and outer layer, the core layer is ensured to be between the inner layer and the outer layer. The structure and performance of the film are optimized by using additives such as improved heat sealing materials, lifting agents, slippers, anti-adhesive agents and degrading agents.
It realizes the high sealing, softness and good optical properties of the cigarette soft box packaging film, and has degradable characteristics, and is suitable for cigarette box packaging of different shapes and sizes.
Smart Images

Figure CN119748800A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a three-layer co-extruded film for cigarette soft box packaging, and belongs to the technical field of biaxially stretched polypropylene films. Background Art
[0002] At present, the cigarette packaging film used at home and abroad is mainly biaxially oriented polypropylene film, but domestic customers have stricter requirements for this film than foreign customers. Foreign customers focus on the smooth operation of this film on packaging equipment. As long as the film can stably pass through the packaging machine without problems such as jamming, it is usually considered to meet the requirements. However, in the domestic market, in addition to requiring the film to run smoothly on the packaging equipment, customers also pay special attention to the sealing performance of the film. This is because domestic cigarette factories want to ensure that each pack of cigarettes has excellent sealing to reduce the risk of air leakage, prevent the products in the package from being affected by the external environment (such as moisture, oxygen, microbial invasion, etc.), and maintain the taste and freshness of the cigarettes.
[0003] The smooth operation and good sealing of the film are directly related to the packaging quality of cigarette products. The packaging quality not only affects the appearance of cigarettes, but also affects their preservation effect during storage. The sealing performance of the packaging film represents whether the cigarettes can effectively maintain their original fragrance during storage and transportation after leaving the factory. Good sealing can prevent the loss of flavor components in cigarettes and prevent the fragrance from fading during storage, which is crucial to the consumer experience. Therefore, sealing has become the core technical indicator of domestic cigarette packaging materials. Packaging materials with good sealing performance can not only enhance consumers' sensory experience of cigarettes, but also protect product quality and reduce complaints caused by poor packaging.
[0004] Soft pack refers to a form of cigarette packaging using soft paper materials. Compared with hard pack, the main feature of soft pack is that the packaging material is soft and comfortable to the touch. Therefore, if soft pack cigarettes are to be packaged, it is necessary not only to ensure the sealing performance, but also to take into account the softness of the film. At the same time, hard pack cigarettes have a more obvious buffer pressure, and elasticity can be used to help the film seal better during heat sealing. Soft pack cigarette packaging is different. Since soft boxes have no buffer pressure, the box body is soft and lacks elasticity, it is much more difficult to achieve a good sealing effect for soft box cigarette packaging than hard boxes. At present, only polyethylene film can achieve good sealing performance, but the use of polyethylene material is limited by low softness, and its heat shrinkage rate is too high, which is not suitable for soft box packaging of cigarettes.
[0005] In addition, the existing cigarette packaging film is usually a film made by a three-layer co-extruded polypropylene biaxial stretching process. The three-layer structure includes an inner layer, a core layer and an outer layer. The optical properties of the film are determined by the inner layer, the core layer and the outer layer. For soft packaging films, higher gloss and lower haze are required to provide a good appearance. However, both the existing polyethylene film and the polypropylene film have poor optical properties.
[0006] In summary, the present invention aims to develop a method for preparing a soft-pack film for cigarettes that can be smoothly loaded onto a machine, has good sealing performance, and has both softness and good optical properties. Summary of the invention
[0007] To solve the above problems, the present invention provides a method for preparing a three-layer co-extruded film for cigarette soft box packaging. Through the synergistic effect of different formula components and processes, while achieving good sealing, the biaxially stretched film has good softness, optical properties and degradable characteristics.
[0008] The first object of the present invention is to provide a method for preparing a three-layer co-extruded film, comprising the following steps:
[0009] S1. Prepare the raw materials of each layer according to the inner layer formula, core layer formula and outer layer formula respectively;
[0010] S2, using a three-layer co-extrusion biaxial stretching process to prepare the raw materials of each layer in step S1 into a film with a three-layer structure, wherein the core layer is located between the inner layer and the outer layer;
[0011] Based on the mass percentage of the inner layer being 100%, the inner layer formula comprises: 50%-95% of heat sealing material and 7%-50% of the first additive;
[0012] Based on the mass percentage of the core layer being 100%, the core layer formula comprises: 50%-90% propylene homopolymer, 10%-30% ethylene acrylic acid copolymer, and 6%-40% second additive;
[0013] Based on the mass percentage of the outer layer being 100%, the outer layer formula comprises: 50%-95% of heat sealing material and 7%-50% of the third additive;
[0014] The heat sealing material is composed of ion polymer, polybutylene resin and ethylene acrylic acid copolymer in a mass ratio of (4-6): (2-4): 2.
[0015] Furthermore, at least one of the following is included:
[0016] (1) The ionic polymer is selected from Surlyn 1706 of Chemours Company;
[0017] (2) The molecular weight of the polybutene resin is 150,000-250,000; preferably, Innovene PB-1 from INEOS;
[0018] (3) The molecular weight of the ethylene acrylic acid copolymer is 80,000-150,000; preferably Nucrel from DuPont;
[0019] (4) The molecular weight of the propylene homopolymer is 300,000-400,000; preferably PP520L produced by Sabic.
[0020] Furthermore, at least one of the following is included:
[0021] (1) Based on the mass percentage of the inner layer being 100%, the first additive comprises 5%-50% of a stiffening agent, 1%-5% of a slip agent, 1%-5% of an anti-blocking agent, and 0%-10% of a degradation agent;
[0022] (2) based on the mass percentage of the core layer being 100%, the second additive comprises 5%-35% of a stiffening agent, 1%-10% of an antistatic agent, and 0%-10% of a degradation agent;
[0023] (3) Based on the mass percentage of the outer layer being 100%, the third additive comprises 5%-50% of a stiffening agent, 1%-5% of a slip agent, 1%-5% of an anti-blocking agent, and 0%-10% of a degradation agent.
[0024] Furthermore, at least one of the following is included:
[0025] (1) The stiffening agent contains 40-70 wt % of hydrogenated petroleum resin and 30-60 wt % of propylene homopolymer;
[0026] (2) The lubricant includes polydimethylsiloxane;
[0027] (3) the anti-adhesive agent comprises at least one of silicon dioxide, polymethyl methacrylate and polymethylsilsesquioxane;
[0028] (4) the antistatic agent comprises at least one of fatty acid esters, ethoxylated alkylamines, diethanolamides and ethoxylated alcohols;
[0029] (5) The degradation agent includes a TDPA degradation agent.
[0030] Furthermore, the thickness ratio of the inner layer, the core layer and the outer layer is (0.5-3):(11-21):(0.5-3).
[0031] Furthermore, the three-layer co-extrusion biaxial stretching process includes a three-layer co-extrusion process and a biaxial stretching process;
[0032] The three-layer co-extrusion process includes the steps of heating the raw materials of each layer to form a molten raw material and extruding it simultaneously;
[0033] The biaxial stretching step includes the steps of longitudinal stretching preheating, longitudinal stretching, longitudinal stretching shaping, transverse stretching preheating, transverse stretching, and transverse stretching shaping.
[0034] Furthermore, at least one of the following is included:
[0035] (1) The preheating temperature for longitudinal stretching is 100°C-150°C; most preferably, it is between 105°C-145°C;
[0036] (2) The longitudinal stretching temperature is 90°C-130°C; most preferably between 96°C-121°C;
[0037] (3) The temperature for longitudinal stretching and shaping is 100°C-155°C; most preferably, it is between 110°C-146°C;
[0038] (4) The longitudinal stretch ratio is 4.0-6.0; most preferably 5.0-5.4;
[0039] (5) The preheating temperature for transverse stretching is 150°C-180°C;
[0040] (6) The temperature of transverse stretching is 130°C-175°C;
[0041] (7) The temperature for transverse stretching and shaping is 105°C-125°C.
[0042] The second object of the present invention is to provide a three-layer co-extruded film prepared by the above preparation method.
[0043] The third object of the present invention is to provide the use of the three-layer co-extruded film in preparing packaging materials.
[0044] A fourth object of the present invention is to provide a film for cigarette soft box packaging, wherein the film comprises at least one layer of the three-layer coextruded film.
[0045] Beneficial effects of the present invention:
[0046] The present invention provides a cigarette packaging film, which has the following advantages:
[0047] (1) By improving the use of heat-sealing materials, the sealing temperature is reduced, the heat-sealing temperature range is expanded, and the heat-sealing strength is significantly improved, providing good sealing for the soft box packaging after heat sealing;
[0048] (2) By improving the raw materials of different layers, especially the raw materials of the core layer, the prepared film has better softness, can better fit the surface of the cigarette box, and can also adapt to cigarette boxes of different shapes and sizes, ensuring the tightness and uniformity of the packaging. In addition, the soft film can also reduce friction and loss during processing;
[0049] (3) Through the coordination of different layer formulas and processes, the interface and internal uniformity are improved. The film of the present invention has good optical properties, can provide a clearer bottom display effect, enhance the visual brightness, and improve the sensory experience of consumers;
[0050] (4) Degradants are added to the formula, and the adverse effects of the introduction of the degradants are greatly reduced through optimization, providing the film with degradable properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 It is a schematic diagram of the film structure of the present invention.
[0052] Figure 2 This is a processing diagram. DETAILED DESCRIPTION
[0053] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0054] The materials involved in the present invention are as follows:
[0055]
[0056] The scheme involved in the present invention is as follows:
[0057] The present invention provides a high-sealability soft box packaging film for cigarettes, comprising an inner layer, a core layer and an outer layer, wherein the core layer is arranged between the inner layer and the outer layer.
[0058] The inner layer includes propylene modified heat sealing material and additives, including:
[0059] Improved heat sealing materials account for 50% to 95%.
[0060] Stiffener 5% to 50%,
[0061] Lubricant 1% to 5%,
[0062] Anti-adhesive agent 1% to 5%,
[0063] Degradants 0% to 10%;
[0064] The core layer comprises a propylene homopolymer and additives, including:
[0065] Propylene homopolymer accounts for 50% to 90%,
[0066] Ethylene acrylic acid copolymer accounts for 10% to 30%,
[0067] Stiffener 5% to 35%,
[0068] Antistatic agent 1% to 10%,
[0069] Degradants 0% to 10%;
[0070] The outer layer includes improved heat sealing materials and additives, including:
[0071] Improved heat sealing materials account for 50% to 95%.
[0072] Stiffener 5% to 50%,
[0073] Lubricant 1% to 5%,
[0074] Anti-adhesive agent 1% to 5%,
[0075] Degradants 0% to 10%.
[0076] in:
[0077] Improved heat sealing material is a specially formulated material, which is obtained by mixing three raw materials in a specific ratio. It includes ion polymer (MFI = 0.5-0.9g / 10min@190℃, 2.16kg), polybutylene resin (MFI = 2.8-3.2g / 10min@190℃, 2.16kg), and ethylene acrylic acid copolymer (MFI = 5.8-6.2g / 10min@190℃, 2.16kg), and the mass ratio of the three is (4-6): (2-4): 2.
[0078] The stiffening agent is prepared from 40-70wt% hydrogenated petroleum resin and 30-60wt% propylene homopolymer, with a melt mass flow rate MFR≥25g / 10min, wherein the MFI value of the propylene homopolymer is 2.5-9.0g / 10min, and the isotacticity is above 95%.
[0079] The lubricant is polydimethylsiloxane, and the melt mass flow rate MFR is 2.5-9.0 g / 10 min.
[0080] The anti-adhesive agent is synthetic silica, polymethyl methacrylate or polymethylsilsesquioxane, and the melt mass flow rate MFR is 2.5-9.0 g / 10 min.
[0081] The antistatic agent is fatty acid ester, ethoxylated alkylamine, diethanolamide or ethoxylated alcohol, and the melt mass flow rate MFR is 15-50 g / 10 min.
[0082] The degradation agent may be any degradation agent that does not affect film formation, preferably a metal salt, such as the degradation agent used in the present invention.
[0083] The MFI (MeltFlow Index) of the heat sealing materials mentioned above is an important parameter to measure the flow properties of the material in the molten state, also known as MFR. The higher the MFI value, the better the flow properties of the material in the molten state, which is very important for the heat sealing process. Good flow properties ensure that the heat sealing material flows evenly and fits tightly during heat sealing, thus forming a firm seal.
[0084] The present invention improves the heat-sealing material, and a certain proportion of ionomer, polybutene resin and ethylene acrylic acid copolymer are compounded to form a new heat-sealing material formula. The film prepared by co-extrusion and stretching after melting the formula can at least take into account heat-sealing performance and softness. Among them, the ionomer selected by the present invention has excellent melt strength, clarity, softness and toughness, and can show excellent heat-sealing performance even at a relatively low heat-sealing starting temperature. Polybutene resin has excellent heat resistance, transparency and non-toxicity. Ethylene acrylic acid copolymer (EAA) has good heat-sealing properties and can achieve effective heat sealing at a relatively low temperature. Moreover, EAA has extremely high adhesion to a variety of materials, making it an ideal choice in packaging applications.
[0085] The present invention finds that, although the commonly used polypropylene film, polyethylene film or ethylene acrylic acid copolymer film has good sealing performance, it is limited in application in cigarette soft packs, especially in terms of optical performance and softness. The present invention achieves a balance of these properties through appropriate combination and proportion with appropriate process. Specifically:
[0086] As we all know, when preparing thin films, the first thing to consider is whether the selected formula can form a film. Whether a film can form a film depends on at least several aspects: the formula and process conditions and the matching of raw materials and processes. (1) If the formula design is unreasonable, including but not limited to the type of raw materials, the ratio of raw materials, the type and ratio of additives, etc., it may lead to the failure of film formation. When the raw materials in the formula are unreasonable, not only will the optical properties of the film deteriorate, but also material shedding or even film breakage will occur during the stretching process. (2) The parameters in the film-forming process, especially the stretching process in the three-layer co-extrusion process, will affect the formation of the film. The stretching process includes longitudinal preheating, longitudinal stretching, transverse preheating, transverse stretching and other processes. The appropriate process will cause the originally disordered polymer materials in the formula to rearrange during the stretching process. The various interactions between the polymer chains will play a role in this process and promote neatness. Different raw materials can achieve different stretching effects, which affects the performance of the film.
[0087] Secondly, the optical properties of the film are determined by the inner layer, the core layer and the outer layer. Therefore, the present invention adjusts the formulation of different layers to improve the optical properties of the film. The optical properties are not only related to the connection at the interface of each layer, but also affected by the uniformity of each layer, such as the stretching process mentioned above and the movement of the polymer chains therein.
[0088] The present invention provides a method for preparing a three-layer co-extruded film, the preparation method comprising the following steps:
[0089] S1. Mix the raw materials of each layer according to the inner layer formula, core layer formula and outer layer formula respectively;
[0090] S2, using a three-layer co-extrusion biaxial stretching process to prepare the raw materials of each layer in step S1 into a film with a three-layer structure, wherein the core layer is located between the inner layer and the outer layer;
[0091] Based on the mass percentage of the inner layer being 100%, the inner layer formula comprises: 50%-95% of heat sealing material and 7%-50% of the first additive;
[0092] Based on the mass percentage of the core layer being 100%, the core layer formula comprises: 50%-90% propylene homopolymer, 10%-30% ethylene acrylic acid copolymer, and 6%-40% second additive;
[0093] Based on the mass percentage of the outer layer being 100%, the outer layer formula comprises: 50%-95% of heat sealing material and 7%-50% of the third additive;
[0094] The heat sealing material is composed of ion polymer, polybutylene resin and ethylene acrylic acid copolymer in a mass ratio of (4-6): (2-4): 2.
[0095] Preferably, at least one of the following is included:
[0096] (1) The ionic polymer is selected from Surlyn 1706 of Chemours Company;
[0097] (2) The molecular weight of the polybutene resin is 150,000-250,000; preferably, Innovene PB-1 from INEOS;
[0098] (3) The molecular weight of the ethylene acrylic acid copolymer is 80,000-150,000; preferably Nucrel from DuPont;
[0099] (4) The molecular weight of the propylene homopolymer is 300,000-400,000; preferably PP520L produced by Sabic.
[0100] Preferably, based on 100% by mass of the inner layer, the first additive includes 5%-50% of a stiffening agent, 1%-5% of a slip agent, 1%-5% of an anti-blocking agent, and 0%-10% of a degradation agent.
[0101] The stiffening agent is 5%-50%, for example 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, etc., including but not limited to the percentages listed above, preferably 10%-30%.
[0102] The lubricant is 1%-5%, such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc., including but not limited to the percentages listed above.
[0103] The anti-adhesion agent is 1%-5%, such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc., including but not limited to the percentages listed above.
[0104] The degradation agent is 0%-10%, for example 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, etc., including but not limited to the percentages listed above, preferably 1%-5%.
[0105] Those skilled in the art can understand that in order to make the material more convenient to process and to achieve the general properties required of the material, a stiffening agent, a slip agent and an anti-blocking agent are generally added to the inner layer. The present invention is in line with the concept of green environmental protection and adds a degradation agent thereto. However, it has been found through experiments that although the addition of a degradation agent can increase the degradation rate, it will affect the film properties, such as changing the mechanical properties of the film and reducing the thermal stability of the film. In order to improve the effect of the degradation agent on the heat sealing performance of the film, the present invention, on the one hand, selects a metal salt degradation agent from TDPA, and on the other hand, adjusts the formula to reduce the adverse effects of the degradation agent.
[0106] Preferably, based on 100% by mass of the core layer, the second additive includes 5%-35% of a stiffening agent, 1%-10% of an antistatic agent, and 0%-10% of a degradation agent.
[0107] The stiffening agent is 5%-35%, such as 10%, 15%, 20%, 25%, 30%, etc., including but not limited to the percentages listed above, preferably 15%-25%.
[0108] The antistatic agent is 1%-10%, for example 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, etc., including but not limited to the percentages listed above, preferably 3%-8%.
[0109] The degradation agent is 0%-10%, for example 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, etc., including but not limited to the percentages listed above, preferably 1%-5%.
[0110] Preferably, based on 100% by mass of the outer layer, the third additive includes 5%-50% of a stiffening agent, 1%-5% of a slip agent, 1%-5% of an anti-blocking agent, and 0%-10% of a degradation agent.
[0111] The stiffening agent is 5%-50%, for example 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, etc., including but not limited to the percentages listed above, preferably 10%-30%.
[0112] The lubricant is 1%-5%, such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc., including but not limited to the percentages listed above, preferably 1%-4%.
[0113] The anti-adhesion agent is 1%-5%, such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, etc., including but not limited to the percentages listed above, preferably 1%-4%.
[0114] The degradation agent is 0%-10%, for example 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, etc., including but not limited to the percentages listed above, preferably 1%-5%.
[0115] Preferably, the heat sealing material is 50%-95% in the inner layer formula, and the heat sealing material is 50%-95% in the outer layer formula. For example, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., including but not limited to the percentages listed above, preferably 60%-80%, and most preferably 60%-70%. The heat sealing material provides a heat sealing effect for the film, which is mainly achieved by adding a certain amount of heat sealing material to the inner and outer surfaces of the film. When heated, the heat sealing material will first melt and flow due to its low melting point, many segments and side chains, and then after a certain pressure, the heat sealing material molecules on the surface of the film will entangle with each other and change their arrangement through molecular motion to form a heat-sealed state. The selection of a suitable heat sealing material formula can improve the heat sealing strength, sealing temperature and heat sealing temperature range of the film.
[0116] Preferably, in the core layer formulation, the propylene homopolymer (ternary) is 50%-90%, such as 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., including but not limited to the percentages listed above, preferably 50%-60%. Adding propylene homopolymer to the core layer can not only increase the overall strength and stiffness of the film, but also has better flow characteristics, which is conducive to the extrusion process of the film.
[0117] Preferably, in the core layer formula, ethylene acrylic acid copolymer is 10%-30%, such as 15%, 20%, 25%, etc., including but not limited to the percentages listed above. The present invention adds ethylene acrylic acid copolymer to the core layer not only because EAA has good adhesion and heat sealing properties, but also because: the present invention adds a certain proportion of EAA to both the inner layer and the outer layer. During the processing, due to molecular motion and the existence of intermolecular forces (such as hydrogen bonding), the compatibility between the core layer and the inner layer and the outer layer can be promoted, and the interface joint is smoother, achieving the purpose of improving the interface, which can concentrate the reflection of light and improve the gloss; at the same time, the distribution of components in each layer is more uniform, reducing internal heterogeneity, reducing light scattering, and reducing haze, thereby providing the film with good optical properties and heat sealing properties.
[0118] Preferably, the thickness ratio of the inner layer, the core layer and the outer layer is (0.5-3): (11-21): (0.5-3), such as 1:15:1, 1:15:2, 2:15:1, etc., including but not limited to the ratios listed above, and the thickness of each layer can be controlled by adjusting the weight of the formula. Most preferably, the inner layer is 0.5-3.0 μm thick, the core layer is 11-21 μm thick, the outer layer is 0.5-3.0 μm thick, and the thickness of the film ranges from 17 μm to 28 μm.
[0119] The three-layer co-extrusion biaxial stretching process of the present invention is a plastic processing process, which is to extrude three different molten materials (i.e., the inner layer formula, core layer formula and outer layer formula in the present invention) through a co-extrusion head at the same time and tightly combine them together to form a composite material product with specific functions (such as Figure 2 ).
[0120] Preferably, the present invention specifically comprises the following steps:
[0121] (1) Melt extrusion: The raw material is heated in an extruder to melt it, forming a molten raw material, which is then extruded through the screw of the extruder;
[0122] (2) Stretching film: The extruded product is introduced into a stretching and orienting machine, and the film is stretched by adjusting the temperature and speed to change the mechanical properties and physical properties of the film;
[0123] (3) Shaping: The film needs to be cooled quickly after stretching and solidifying. During the cooling and shaping process, the width and thickness of the film can be controlled by adjusting the temperature of the cooling water tank and the stretching speed.
[0124] The multi-layer co-extrusion extrusion machine of the present invention can be a widely used step-by-step stretching BOPP machine, or a synchronous stretching BOPP machine. In the above process, the specifications of the extruder for BOPP auxiliary extrusion are particularly required: the extruder screw used for auxiliary extrusion is a twin screw, the screw diameter is 60mm, and the aspect ratio is 35. The material of the longitudinal stretching preheating roller and the stretching roller is thickened Teflon, with a total thickness of 100μm.
[0125] Preferably, the three-layer co-extrusion biaxial stretching process includes a three-layer co-extrusion step and a biaxial stretching step, and the biaxial stretching step includes: longitudinal stretching preheating, longitudinal stretching, longitudinal stretching shaping, transverse stretching preheating, transverse stretching, and transverse stretching shaping. The biaxial stretching process will affect the softness, heat sealing performance and optical properties of the film. The key lies in the matching of the parameters of the longitudinal stretching section (MDO) and the transverse stretching section (TDO). Therefore, this process is particularly important in the preparation. Specifically: (1) Softness is an indicator for evaluating the performance of soft packaging films, among which molecular orientation is related to the softness of the film. During the stretching process, the molecules are oriented in the longitudinal direction (MD) and the transverse direction (TD). As the formula changes, the orientation parameters of the molecules along different directions will change accordingly, thereby adjusting the softness of the film. In the present invention, through the synergistic combination of different substances, it is found that the Young's modulus of the final product is significantly reduced, providing the required softness. (2) In addition to the formula of the heat sealing material, temperature also has a significant effect on the heat sealing strength. The process steps include melt extrusion-stretching film-setting. As mentioned above, the stretching process involves the movement and arrangement of molecular chains, and the temperature during the stretching process will undoubtedly affect the movement of molecular chains. The same is true for the setting temperature. The combination of the two determines the heat sealing performance of the film. (3) Similarly, the temperature during preheating and stretching will affect the movement and arrangement of molecular chains, affect the uniformity of the interface and between layers, and thus affect the optical properties of the film.
[0126] Preferably, at least one of the following is included:
[0127] (1) The preheating temperature for longitudinal stretching is 100°C-150°C; most preferably, it is between 105°C-145°C;
[0128] (2) The longitudinal stretching temperature is 90°C-130°C; most preferably between 96°C-121°C;
[0129] (3) The temperature for longitudinal stretching and shaping is 100°C-155°C; most preferably, it is between 110°C-146°C;
[0130] (4) The longitudinal stretch ratio is 4.0-6.0; most preferably 5.0-5.4;
[0131] (5) The preheating temperature for transverse stretching is 150°C-180°C;
[0132] (6) The temperature of transverse stretching is 130°C-175°C;
[0133] (7) The temperature for transverse stretching and shaping is 105°C-125°C.
[0134] The present invention also provides a film for cigarette soft box packaging, the film comprising at least one layer of three-layer co-extruded film prepared by the above preparation method. The film provided by the present invention has good softness and heat shrinkage performance, does not cause squeezing of the cigarette box in the package when used for cigarette packaging, has more relaxed requirements on the material of the cigarette box, and is suitable for the packaging of soft pack cigarette boxes.
[0135] Example 1
[0136] (1) The formula of each layer of the soft box packaging film is as follows (by mass ratio):
[0137] Roller layer (inner layer): improved heat sealing material 66%, MFI of improved heat sealing material = 2.0g / 10min; stiffening agent 20%, MFI of stiffening agent = 40g / 10min; slip agent 4%, MFI of slip agent = 5.2g / 10min; anti-blocking agent 5%; TDPA degradation agent 5%.
[0138] Core layer: 55% propylene homopolymer, MFI of propylene homopolymer=3.0g / 10min; 15% ethylene acrylic acid copolymer (molecular weight 80000); 20% stiffening agent; 5% antistatic agent; 5% TDPA degradation agent.
[0139] Air knife layer (outer layer): improved heat sealing material 66%, MFI of improved heat sealing material = 2.0g / 10min; stiffening agent 20%; slip agent 5%; anti-blocking agent 4%, MFI of anti-blocking agent = 5.9g / 10min; TDPA degradation agent 5%.
[0140] in:
[0141] Improved heat sealing material: by mass percentage, it is composed of 50% ion polymer (MFI = 0.7 g / 10min@190°C, 2.16kg), 30% polybutene resin (MFI = 3.0 g / 10min@190°C, 2.16kg, molecular weight 200000), and 20% ethylene acrylic acid copolymer (MFI = 6.0 g / 10min@190°C, 2.16kg, molecular weight 80000), and is extruded using a mixing extruder.
[0142] Stiffener: A mixture of 50% hydrogenated petroleum resin and 50% propylene homopolymer.
[0143] The lubricant is polydimethylsiloxane.
[0144] The anti-blocking agent is synthetic silica.
[0145] The antistatic agent is fatty acid ester.
[0146] (2) The three-layer co-extrusion polypropylene biaxial stretching process is used for preparation. The process flow includes: mixing of raw materials, extrusion, longitudinal stretching preheating, longitudinal stretching (MDO), shaping, transverse stretching preheating, transverse stretching (TDO), shaping, and winding. Among them, the production process parameters are:
[0147] MDO preheating temperature: 120℃; MDO stretching temperature: 97℃; MDO setting temperature: 120℃; MDO total stretching ratio is 5.2;
[0148] TDO preheating temperature: 172°C; TDO stretching temperature: 145°C; TDO setting temperature: 110°C; TDO speed setting value 170m / min.
[0149] Finally, the soft-package film product was obtained with a total thickness of 21 μm, a roller layer thickness of 0.9 μm, a core layer thickness of 18.9 μm, and an air knife layer thickness of 1.2 μm.
[0150] Example 2
[0151] Adjust the process parameters of three-layer co-extruded polypropylene biaxial stretching, and the rest is the same as in Example 1. The production process parameters for the three-layer co-extruded polypropylene biaxial stretching process are:
[0152] MDO preheating temperature: 115°C; MDO stretching temperature: 98°C; MDO setting temperature: 110°C; MDO total stretching ratio is 5.0;
[0153] TDO preheating temperature: 172°C; TDO stretching temperature: 145°C; TDO setting temperature: 110°C; TDO speed setting value 170m / min.
[0154] Finally, the soft-package film product was obtained, with a total thickness of 21 μm, a roller layer thickness of 1.2 μm, a core layer thickness of 18.3 μm, and an air knife layer thickness of 1.5 μm.
[0155] Example 3
[0156] Adjust the process parameters of three-layer co-extruded polypropylene biaxial stretching, and the rest is the same as in Example 1. The production process parameters for the three-layer co-extruded polypropylene biaxial stretching process are:
[0157] MDO preheating temperature: 105°C; MDO stretching temperature: 98°C; MDO setting temperature: 110°C; MDO total stretching ratio is 4.5;
[0158] TDO preheating temperature: 172°C; TDO stretching temperature: 146°C; TDO setting temperature: 110°C; TDO speed setting value 170m / min.
[0159] Finally, the soft-package film product was obtained with a total thickness of 21 μm, a roller layer thickness of 1.5 μm, a core layer thickness of 17.7 μm, and an air knife layer thickness of 1.8 μm.
[0160] Example 4
[0161] The formula of each layer of the soft box packaging film is adjusted, and the rest is the same as Example 2. The formula of each layer of the soft box packaging film is as follows (by mass ratio):
[0162] Roller layer (inner layer): improved heat sealing material 50%; stiffening agent 47%; slip agent 1%; anti-blocking agent 1%; TDPA degradation agent 1%.
[0163] Core layer: propylene homopolymer 79%; ethylene acrylic acid copolymer 10% (molecular weight 80000); stiffening agent 9%; antistatic agent 1%; TDPA degradation agent 1%.
[0164] Air knife layer (outer layer): improved heat sealing material 80%; stiffening agent 10%; slip agent 4%; anti-blocking agent 4%; TDPA degradation agent 2%.
[0165] in:
[0166] Improved heat sealing material: by mass percentage, it is composed of 50% ion polymer (MFI = 0.7 g / 10min@190°C, 2.16kg), 30% polybutene resin (MFI = 3.0 g / 10min@190°C, 2.16kg, molecular weight 200000), and 20% ethylene acrylic acid copolymer (MFI = 6.0 g / 10min@190°C, 2.16kg, molecular weight 80000), and is extruded using a mixing extruder.
[0167] Stiffener: A mixture of 50% hydrogenated petroleum resin and 50% propylene homopolymer.
[0168] The lubricant is polydimethylsiloxane.
[0169] The anti-blocking agent is synthetic silica.
[0170] The antistatic agent is fatty acid ester.
[0171] Example 5
[0172] The formula of each layer of the soft box packaging film is adjusted, and the rest is the same as Example 2. The formula of each layer of the soft box packaging film is as follows (by mass ratio):
[0173] Roller layer (inner layer): improved heat sealing material 85%; stiffening agent 12%; slip agent 1%; anti-blocking agent 1%; TDPA degradation agent 1%.
[0174] Core layer: propylene homopolymer 60%; ethylene acrylic acid copolymer 30% (molecular weight 80000); stiffening agent 8%; antistatic agent 1%; TDPA degradation agent 1%.
[0175] Air knife layer (outer layer): improved heat sealing material 50%; stiffening agent 40%; slip agent 4%; anti-blocking agent 4%; TDPA degradation agent 2%.
[0176] in:
[0177] Improved heat sealing material: by mass percentage, it is composed of 50% ion polymer (MFI = 0.7 g / 10min@190°C, 2.16kg), 30% polybutene resin (MFI = 3.0 g / 10min@190°C, 2.16kg, molecular weight 200000), and 20% ethylene acrylic acid copolymer (MFI = 6.0 g / 10min@190°C, 2.16kg, molecular weight 80000), and is extruded using a mixing extruder.
[0178] Stiffener: A mixture of 50% hydrogenated petroleum resin and 50% propylene homopolymer.
[0179] The lubricant is polydimethylsiloxane.
[0180] The anti-blocking agent is synthetic silica.
[0181] The antistatic agent is fatty acid ester.
[0182] Example 6
[0183] The composition of the improved heat sealing material is adjusted, and the rest is the same as in Example 2. Wherein: the improved heat sealing material is prepared by weight percentage from 40% ionomer (MFI = 0.7 g / 10min @ 190°C, 2.16 kg), 40% polybutene resin (MFI = 3.0 g / 10min @ 190°C, 2.16 kg, molecular weight 200000), and 20% ethylene acrylic acid copolymer (MFI = 6.0 g / 10min @ 190°C, 2.16 kg, molecular weight 80000), and is obtained by extrusion using a mixing extruder.
[0184] Example 7
[0185] The composition of the improved heat sealing material is adjusted, and the rest is the same as in Example 2. Wherein: the improved heat sealing material is prepared by weight percentage from 60% ionomer (MFI = 0.7 g / 10min @ 190°C, 2.16 kg), 20% polybutene resin (MFI = 3.0 g / 10min @ 190°C, 2.16 kg, molecular weight 200000), and 20% ethylene acrylic acid copolymer (MFI = 6.0 g / 10min @ 190°C, 2.16 kg, molecular weight 80000), and is obtained by extrusion using a mixing extruder.
[0186] Example 8
[0187] The polybutene resin in the improved heat sealing material is replaced by a polybutene resin with an average molecular weight of 150,000, and the remaining steps are the same as those in Example 2.
[0188] Example 9
[0189] The ethylene acrylic acid copolymer in the improved heat sealing material was replaced with an ethylene acrylic acid copolymer with an average molecular weight of 150,000, and the remaining steps were the same as in Example 2.
[0190] Comparative Example 1
[0191] The improved heat sealing material in the roller layer is replaced with a propylene homopolymer, the ethylene acrylic acid copolymer in the core layer is replaced with a propylene homopolymer, and the improved heat sealing material in the air knife layer is replaced with a propylene homopolymer. The remaining steps are the same as in Example 2.
[0192] Comparative Example 2
[0193] The ionomer in the improved heat-sealing material was replaced with a propylene homopolymer, and the remaining steps were the same as in Example 2.
[0194] Comparative Example 3
[0195] The ethylene acrylic acid copolymer in the improved heat sealing material was replaced by a propylene homopolymer, and the remaining steps were the same as in Example 2.
[0196] Comparative Example 4
[0197] The improved heat sealing material in the roller layer is replaced with ethylene acrylic acid copolymer, the ethylene acrylic acid copolymer in the core layer is replaced with ethylene acrylic acid copolymer, and the improved heat sealing material in the air knife layer is replaced with ethylene acrylic acid copolymer. The remaining steps are the same as Example 2.
[0198] Comparative Example 5
[0199] The improved heat sealing material in the roller layer is replaced with polyethylene, the ethylene acrylic acid copolymer in the core layer is replaced with polyethylene, and the improved heat sealing material in the air knife layer is replaced with polyethylene. The remaining steps are the same as in Example 2.
[0200] Comparative Example 6
[0201] The ethylene acrylic acid copolymer in the core layer was replaced with a propylene homopolymer, and the remaining steps were the same as in Example 2.
[0202] Comparative Example 7
[0203] The amounts of propylene homopolymer and ethylene acrylic acid copolymer in the core layer were adjusted to 30% of propylene homopolymer and 40% of ethylene acrylic acid copolymer. The remaining steps were the same as those in Example 2.
[0204] Comparative Example 8
[0205] The polybutene resin in the improved heat sealing material is replaced by a polybutene resin with an average molecular weight of 10,000, and the remaining steps are the same as those in Example 2.
[0206] Comparative Example 9
[0207] The polybutene resin in the improved heat sealing material is replaced by a polybutene resin with an average molecular weight of 500,000, and the remaining steps are the same as those in Example 2.
[0208] Comparative Example 10
[0209] The ethylene acrylic acid copolymer in the improved heat sealing material was replaced with an ethylene acrylic acid copolymer with an average molecular weight of 10,000, and the remaining steps were the same as in Example 2.
[0210] Test Case
[0211] The heat seal starting temperature, heat seal strength, haze, glossiness, and softness of the film products prepared in the above examples and comparative examples were tested respectively. Among them, the testing conditions for the inner-to-inner heat seal starting temperature and the outer-to-outer heat seal starting temperature were: force 150N, time 0.5 seconds; the inner-to-inner heat seal strength, the inner-to-outer heat seal strength, and the outer-to-outer heat seal strength were all tested according to the YC / T 266 testing method; the haze was tested according to the method in GB 2410; the glossiness was tested according to the method in GB 8807; and the softness was tested according to YC / T 266-2008. The results are as follows:
[0212]
[0213] During the preparation process, Comparative Example 8 dropped material during the stretching process, Comparative Examples 2 and 8 were both unable to form films, and the film in Comparative Example 1 turned white.
[0214] The films prepared in Examples 1-3 and Comparative Example 1 were irradiated with UV light at a wavelength of 500 nm for 100 hours, and their tensile strength and elongation at break were tested. The results are as follows:
[0215]
[0216] The present invention uses a simulated light irradiation method to detect the degradation properties of different films. During the light degradation process, the film undergoes oxidative chain scission, changes in the molecular structure, and properties such as tensile strength and elongation at break change with the increase in irradiation time. As can be seen from the above table, after 100 hours of UV irradiation, the tensile strength and elongation at break of the film prepared by the present invention are significantly lower than those of the existing polypropylene film, indicating that it has good degradability.
[0217] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a three-layer co-extruded film, characterized in that: The following steps are involved: S1. Prepare the raw materials of each layer according to the inner layer formula, core layer formula and outer layer formula respectively; S2, using a three-layer co-extrusion biaxial stretching process to prepare the raw materials of each layer of step S1 into a film with a three-layer structure, wherein the core layer is located between the inner layer and the outer layer; Based on the mass percentage of the inner layer being 100%, the inner layer formula comprises: 50%-95% of heat sealing material and 7%-50% of the first additive; Based on the mass percentage of the core layer being 100%, the core layer formula comprises: 50%-90% of propylene homopolymer, 10%-30% of ethylene acrylic acid copolymer, and 6%-40% of the second additive; Based on the mass percentage of the outer layer being 100%, the outer layer formula comprises: 50%-95% of heat sealing material and 7%-50% of the third additive; The heat sealing material is composed of ion polymer, polybutylene resin and ethylene acrylic acid copolymer in a mass ratio of (4-6): (2-4):
2.
2. The preparation method according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The ionic polymer is selected from Surlyn 1706 of Chemours Company; (2) The molecular weight of the polybutene resin is 150,000-250,000; preferably, Innovene PB-1 from INEOS; (3) The molecular weight of the ethylene acrylic acid copolymer is 80,000-150,000; preferably Nucrel from DuPont; (4) The molecular weight of the propylene homopolymer is 300,000-400,000; preferably PP520L produced by Sabic.
3. The preparation method according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) Based on the mass percentage of the inner layer being 100%, the first additive comprises 5%-50% of a stiffening agent, 1%-5% of a slip agent, 1%-5% of an anti-blocking agent, and 0%-10% of a degradation agent; (2) based on the mass percentage of the core layer being 100%, the second additive comprises 5%-35% of a stiffening agent, 1%-10% of an antistatic agent, and 0%-10% of a degradation agent; (3) Based on the mass percentage of the outer layer being 100%, the third additive comprises 5%-50% of a stiffening agent, 1%-5% of a slip agent, 1%-5% of an anti-blocking agent, and 0%-10% of a degradation agent.
4. The preparation method according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The stiffening agent contains 40-70 wt % of hydrogenated petroleum resin and 30-60 wt % of propylene homopolymer; (2) The lubricant includes polydimethylsiloxane; (3) the anti-adhesive agent comprises at least one of silicon dioxide, polymethyl methacrylate and polymethylsilsesquioxane; (4) The antistatic agent comprises at least one of fatty acid esters, ethoxylated alkylamines, diethanolamides and ethoxylated alcohols.
5. The preparation method according to claim 1, characterized in that: The thickness ratio of the inner layer, the core layer and the outer layer is (0.5-3):(11-21):(0.5-3).
6. The preparation method according to claim 1, characterized in that: The three-layer co-extrusion biaxial stretching process includes a three-layer co-extrusion process and a biaxial stretching process; The three-layer co-extrusion process includes the steps of heating the raw materials of each layer to form a molten raw material and extruding it simultaneously; The biaxial stretching step includes the steps of longitudinal stretching preheating, longitudinal stretching, longitudinal stretching shaping, transverse stretching preheating, transverse stretching, and transverse stretching shaping.
7. The preparation method according to claim 6, characterized in that: Contains at least one of the following characteristics: (1) The preheating temperature for longitudinal stretching is 100°C-150°C; (2) The longitudinal stretching temperature is 90°C-130°C; (3) The temperature for longitudinal stretching and shaping is 100°C-155°C; (4) longitudinal stretching ratio of 4.0-6.0; (5) The preheating temperature for transverse stretching is 150°C-180°C; (6) The temperature of transverse stretching is 130°C-175°C; (7) The temperature for transverse stretching and shaping is 105°C-125°C.
8. A three-layer co-extruded film prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the three-layer co-extruded film according to claim 8 in preparing packaging materials.
10. A film for cigarette soft box packaging, characterized in that: The film comprises at least one layer of the three-layer coextruded film according to claim 8.
Citation Information
Patent Citations
Moisture barrier film
CN1084452A
Degradable biaxially-oriented polylactic acid cigarette film and preparation method thereof
CN110774714A
Cigarette packaging film with high optical performance and high air tightness and preparation method thereof
CN115503317A
Easily degradable film for cigarettes and preparation method thereof
CN115946418A
Packaging film with improved heat sealability
US4125662A